The main stages of halfcentury of scientific work of laboratory of immunity of agricultural plants to diseases: achievements and future prospects - Lisovyi, M.P.; Lisova, G.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The reduced analysis of scientific activity of laboratory of immunity of agricultural plants to diseases is resulted, executed in 1959—2016. The basic directions of researches, results and achievements which compound a basis of the theory of immunity of plants to diseases, is displayed. Served the vision of the development of scientific achievements in the field of plant immunity in the near future, taking into account characteristics of the current state of science and agrarian production.